Study guides

☆☆

Q: Simplify 4 9 plus 3 7?

Write your answer...

Submit

Still have questions?

Related questions

Do the math. -4 -3 +6 = -7 + 6 = -1

Gather like terms: 2m - m + 3 + 4 = m + 7.

-3

The expression to simplify is 4+6i+7 Answer: 6i + 11

7

3/24 + 4/24 = 7/24

7(a + 3) = 7*a + 7*3 = 7a + 21

answer=3k-3

Actually, I don't really think that you can simplify it, because if you convert them into fractions, there all over 1 and you can't simplify it. You can simplify it if it's: 5 plus 7 DIVIDED by 3. That was when you divide the 12 by 3 in fraction form, the 3 and one switch, and u can simplify 3 into 1 and 12 into four, so there by the answer is 4. (Sorry if confusing)

1/3 + 3/5 + 7/10 = 49/30 or 119/30

11 - 7 1/4 = 3 3/4.

3 + 4 + 7 = 14

2a + 3 - 9b - a - 7 Bring like terms together: = 2a - a - 9b + 3 - 7 Combine like terms: = a - 9b - 4

Simplify (-7/8)(-3/4).

3

3+4=7+0=7

-7 + 2(x-3) = -7+2x-6 = 2x - 13

-7

7

3

-7

3√2 + 5√3 + 4√2 + 7√3 = (3 + 4)√2 + (5 + 7)√3 = 7√2 + 12√3 If further simplification is required then √2 = 1.41421 and √3 =1.73205 (both to 5 dp) Then (7 x 1.414.21) + (12 x 1.73205) = 9.89949 + 20.78461 = 30.68410

4 + 3 = 7 + 4 = 11 + 3 = 14

The answer to 3 plus 4 equals 7

[(7+3)/(x+4)] / [(x-5)/(2-4)] =[(7+3)/(x+4)] * [(2-4)/(x-5)] =[10*(x-5)] / [-2*(x+4)] =-5*[(x-5)/(x+4)]